Marketing of a commercial bank as a tool to ensure food security in the economic system of the state - I. Konovalova; T. Dzambolat; M. A. Vorontsova (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the importance of the marketing activities of a commercial bank for ensuring the country's food security. In modern conditions of changing geopolitical situation, ensuring the country's food security is one of the key aspects of the sustainable state of society. Commercial banks play an important role in solving this problem. Attracted financial resources from individuals and organizations are directed by commercial banks to enterprises of the agro-industrial complex in the form of loans. Statistical data on the lending activities of Sberbank PJSC reflect the prevalence of concessional loans supported by the state. At the same time, there is an opportunity to expand work on concessional lending by attracting free funds from citizens through the intensification of the marketing activities of commercial banks, including PJSC Sberbank. To do this, it is advisable to conduct targeted marketing work with customers, substantiating the importance of ensuring food security for every citizen.